1970
DOI: 10.1002/app.1970.070140603
|View full text |Cite
|
Sign up to set email alerts
|

Energy‐absorbing characteristics of foamed polymers

Abstract: synopsisThe energy-absorbing characteristics of a foam are determined by its load-compression response, and hence reflect the geometric structure and physical properties of the matrix material. In this report, the energy-absorbihg characteristics are expressed in terms of three dimensionless quantities: (1) K , the energy-absorbing efficiency, (2) I , the impact energy per unit volume divided by E,, and (3) I / K , the maximum decelerating force per unit area divided by E,, where E l is the apparent Young's mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 4 publications
0
43
0
Order By: Relevance
“…Each reflects different micro-structural compliance and failure mechanisms. [36,[38][39][40] As already mentioned, the first stage is the linearelastic response of the foam. During this stage, a number of deformation mechanisms occurs with the more dominant ones being the cell wall bending in combination with the compression of the gas contained within the closed foam cells.…”
Section: Non-dimensional Electrical Measurements As a Function Of Strmentioning
confidence: 96%
See 2 more Smart Citations
“…Each reflects different micro-structural compliance and failure mechanisms. [36,[38][39][40] As already mentioned, the first stage is the linearelastic response of the foam. During this stage, a number of deformation mechanisms occurs with the more dominant ones being the cell wall bending in combination with the compression of the gas contained within the closed foam cells.…”
Section: Non-dimensional Electrical Measurements As a Function Of Strmentioning
confidence: 96%
“…MWCNT produced by catalyzed CVD were supplied by Arkema (France). According to the manufacturer, their diameters were 10-15 nm and they were more than 500 nm long, resulting in an aspect ratio (AR) in the range of [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. Previous studies [19,31,32] utilizing the same batch of CNTs showed good mechanical and electrical results for polymer composites.…”
Section: Materials and Experimental Setup 21 Materials And Manufactmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Elastic modulus, yield point, 3 and length of stress plateau 4,5 are the main parameters to be considered in foam design for specific applications.…”
Section: Introductionmentioning
confidence: 99%
“…In closed-cell polyabsorption characteristics of cellular plastics and mers, two components normally contribute to the rubber have been determined by several aumodulus value in compression [9][10][11] : The first is due thors. 14,15 The energy-absorption characteristics of cellular foams have been evaluated by efficiency EPDM 100 100 100 100 100 100 100 100 100 100 100 Silica ---30 30 30 30 ----Carbon black -------3 0 3 0 3 0 3 0 Paraffin oil 2 2 2 9 9 9 9 4 . 5 4 .…”
Section: Introductionmentioning
confidence: 99%